TOWARDS LOCATING THE NIGHT OF DECREE IN RAMADAN MONTHS WITH MATHEMATICAL CALCULATIONS: Received: 03rd January 2024 Revised: 02nd April 2024, 09th April 2024, 12th April 2024, 15th April 2024 Accepted: 05th April 2024 - Salih Hamza Abuelyamen (MATTER: International Journal of Science and Technology, 2024)
The Night of Decree (NOD) is the night when Allah the Glorified and Almighty descended the Holy Quran in Ramadan month; and He (TGAA) weighed this night to be better than thousand months. Muslims used to fast in Ramadan to gain this bounty. However, the location of this night was not explicitly indicated; but according to some narrations from the Prophet Mohammed (BPUH), he said to seek it in some proposed periods and individual nights. The methodology of the research is based on findings from previous research by the author on the construction of the Hijri calendar. The basic information of the previous research was derived from a verse in the Holy Quran from which we hypothesized that each 309 Hijri years equals completely 300 Gregorian years. A standard figure was developed from this equality and accumulated for all months. The monthly accumulated figures were broken down into daily accumulated figures (DAFs) for all Ramadan months in 309 Hijri years, and the NOD was identified from these DAFs. We managed to find the locations of this night, which are not far from what came in the prophetical narrations; moreover we added more information in this respect.